2020
DOI: 10.1021/acs.inorgchem.0c02618
|View full text |Cite
|
Sign up to set email alerts
|

Inception of Co3O4as Microstructural Support to Promote Alkaline Oxygen Evolution Reaction for Co0.85Se/Co9Se8Network

Abstract: Developing electrocatalysts with abundant active sites is a substantial challenge to reduce the overpotential requirement for the alkaline oxygen evolution reaction (OER). In this work, we have aimed to improve the catalytic activity of cobalt selenides by growing them over the self-supported Co3O4 microrods. Initially, Co3O4 microrods were synthesized through annealing of an as-prepared cobalt oxalate precursor. The subsequent selenization of Co3O4 resulted in the formation of a grainy rodlike Co3O4/Co0.85Se/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 83 publications
3
28
0
Order By: Relevance
“…On the one hand, compared with the Co‐based precursor, it is reported that the as‐prepared spinel Co 3 O 4 can facilitate the reconstruction of the sublattice via reducing the energy gap during selenization that further promote the formation of metal selenides. [ 22 ] Noted that the metal selenides possess the better electronic conductivity than the corresponding oxides or sulfides, this advantage can endow us with more room to modulate EM parameter and optimize EMW absorption capacity. On the other hand, the lattice oxygen in spinel Co 3 O 4 can be substituted by the S and Se via ion exchange in the subsequent sulfuration/selenization treatment.…”
Section: Resultsmentioning
confidence: 99%
“…On the one hand, compared with the Co‐based precursor, it is reported that the as‐prepared spinel Co 3 O 4 can facilitate the reconstruction of the sublattice via reducing the energy gap during selenization that further promote the formation of metal selenides. [ 22 ] Noted that the metal selenides possess the better electronic conductivity than the corresponding oxides or sulfides, this advantage can endow us with more room to modulate EM parameter and optimize EMW absorption capacity. On the other hand, the lattice oxygen in spinel Co 3 O 4 can be substituted by the S and Se via ion exchange in the subsequent sulfuration/selenization treatment.…”
Section: Resultsmentioning
confidence: 99%
“…CoV 2 O 6 exhibited 89% efficiency for the OER process (Figure S9), and proton reaction order (ρRHE) determination for OER involving CoV 2 O 6 revealed the reaction to primarily proceed through a proton decoupled electron transfer pathway (Figure S10). 23 To better comprehend the postcatalytic state of the materials, they were first subjected to prolonged chronopotentiometry that showed near-constant performance (Figure S11) followed by structural and morphological investigations. The pXRD patterns of both materials showed a peak at 2θ = ∼11.5°(Figure S12).…”
mentioning
confidence: 95%
“…[16][17][18] There are quite a few literatures on non-precious non-oxide electrocatalyst for alkaline OER application such as Co 4 N, (Co 0.7 Fe 0.3 ) 2 B, (Co x Fe 1-x ) 2 P and Co 0.85 Se/Co 9 Se 8 etc. [19][20][21][22] Thus, non-precious non-oxide electrocatalyst stimulates great attention for alkaline OER.…”
Section: Introductionmentioning
confidence: 99%